Laser induced nucleation of plasmonic nanoparticles on two-dimensional nanosheets for organic photovoltaics. Issue 3 (17th December 2015) - Sygletou, M.; Tzourmpakis, P.; Petridis, C.; Konios, D.; Fotakis, C.; Kymakis, E.; Stratakis, E.
Abstract : A novel top-down and universal optical technique for the effective decoration of two-dimensional (2D) nanosheets (NS), graphene oxide (GO), boron nitride (BN) and tungsten disulfide (WS2 ), with noble metallic nanoparticles (NPs) is reported. Abstract : A novel top-down and universal optical technique for the effective decoration of two-dimensional (2D) nanosheets (NS), graphene oxide (GO), boron nitride (BN) and tungsten disulfide (WS2 ), with noble metallic nanoparticles (NPs) is reported. The NS–NP assemblies were formed under ambient conditions, via a facile, rapid and solution compatible laser assisted process in the presence of a metallic precursor. It is shown that a few seconds of irradiation is sufficient to decorate the NS lattice, while the NP density can be readily controlled upon variation of the irradiation time. It is found that the laser induced anchoring of Au NPs onto the NS basal plane and edges resulted in enhanced light harvesting that is potentially useful for energy conversion and storage applications. To demonstrate the potential of the approach for practical applications, the incorporation of WS2 –Au NP assemblies into the photoactive layer of ternary bulk heterojunction (BHJ) organic photovoltaic (OPV) cells is realized. The power conversion efficiency (PCE) of the binary device consisting of a poly[ N -9′-heptadecanyl-2, 7-carbazole- alt -5, 5-(4′, 7′-di-2-thienyl-2′, 1′, 3′-benzothiadiazole)] (PCDTBT) : [6, 6]-phenyl-C71-butyric-acid-methyl-ester (PC71 BM) blend as the donor–acceptor pair was 5.6%, while after the employment of WS2 –Au NPs the efficiency enhancement of the ternary device was approximately 13% reaching a total PCE of 6.3%. The facile, rapid and room temperature nature of the photo-induced method proposed here provides unique opportunities for the cost-effective synthesis of bulk amounts of NS–NP assemblies in solution for many optoelectronic applications.